Students' Perceptions Of Grammar's Role In Developing Writing Skills - Lutfiyah Lutfiyah; Hardianti Hardianti; Ezik Firmansah (Jurnal Pendidikan Indonesia, 2025)
This study explores students' perceptions of the role of grammar in developing writing skills among college students at Esa Unggul University. It highlights the complexity of writing as a skill influenced by grammatical accuracy, coherence, and students' attitudes toward grammar. Through qualitative research methods, including interviews and analysis of student writing samples, the findings reveal that students recognize grammar as essential for clarity and professionalism in writing. However, many also perceive grammar as burdensome, which can hinder their writing confidence and creativity. The study emphasizes the need for effective grammar instruction that integrates practical application within writing contexts to enhance students' writing proficiency and motivation.